PEMECAHAN LINEAR PROGRAMMING DUA VARIABEL MENGGUNAKAN LOGIKA FUZZY - Asep Saepuloh; Deni Ahmad Jakaria (JUTEKIN (Jurnal Teknik Informatika), 2015)
Fuzzy logic is a methodology of solving the control system to be implemented in a system, ranging from a simple system, small, large, networks, multi-channel PC or workstation. Besides that, it can be implemented in hardware, software or a combination of both. Fuzzy logic provides a simple way to get definitive conclusions based on ketidaksamaran, ambiguity, imprecision, vagueness, or missing information. Fuzzy logic approach is to control the problem impersonation of someone who will make a decision.Linear programming is a way to establish a fast arrangement of a problem with a simple solution. Set of linear programming gives two reasons: (i) a lot of practical problems which can be formed as a linear programming problem, and (ii) no efficient way (eg simplex method) for solving linear programming problems. Linear programming problems is to find the values of a variable that is not known as a linear objective function that dimaksimasikan under the constraints described by linear equations.On fuzzy linear programming, will look a Z value which is the objective function to be optimized so that is subject to the restrictions are modeled using fuzzy sets. Linear programming is solved by fuzzy logic gives more precise results dibandingakan if without using fuzzy logic. This system provides an opportunity or a chance for the development of the system towards better Keyword  : Logic, Fuzzy, Linear, Programming